1987
DOI: 10.1136/pgmj.63.739.361
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotic tetralogy of Fallot in a 77 year old man

Abstract: Summary:We report the clinical details of a 77 year old man with classical tetralogy of Fallot. The patient had clubbing and cyanosis at birth, and exertional squatting in childhood. He was asymptomatic as an adult until the seventh decade, when he developed biventricular failure and had an episode of bacterial endocarditis. He finally died of cerebral infarction and bronchopneumonia following abdominal surgery.In spite of investigations, the diagnosis was not made in life, but only discovered at post-mortem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…4 The pulmonary annulus was 13 mm in this patient, comparable to that reported in the other published cases-(age 45, PVD 10 mm), 4 (age 77, PVD 9 mm). 5 A second common feature is that of LVH as seen in this patient (16 mm); presumably this acts by delaying of shunting from the right to left ventricle. 6 7 LVH may be a late development in the natural history of Fallot and any beneficial effect may not be seen until adult life.…”
Section: Discussionmentioning
confidence: 70%
“…4 The pulmonary annulus was 13 mm in this patient, comparable to that reported in the other published cases-(age 45, PVD 10 mm), 4 (age 77, PVD 9 mm). 5 A second common feature is that of LVH as seen in this patient (16 mm); presumably this acts by delaying of shunting from the right to left ventricle. 6 7 LVH may be a late development in the natural history of Fallot and any beneficial effect may not be seen until adult life.…”
Section: Discussionmentioning
confidence: 70%
“…9 Thomas et al reported the case of a 77-year-old man who remained asymptomatic until death, and the diagnosis of congenital defect was done postmortem. 10 In the case of our patient, survival until 85 was due to favorable anatomy of the tetralogy, especially to the moderate to severe RVOT obstruction that slowed pulmonary hypertension development.…”
Section: Discussionmentioning
confidence: 66%
“…Thomas et al. reported the case of a 77‐year‐old man who remained asymptomatic until death, and the diagnosis of congenital defect was done postmortem 10 …”
Section: Discussionmentioning
confidence: 99%
“…Iga et al reported the case of a 61‐year‐old woman with tetralogy of Fallot and dextrocardia with situs inversus who was able to survive to this age because of unusually low systemic pressures and a proper balance between VSD and pulmonary stenosis 15 . Chin et al similarly reported the case of a 61‐year‐old man, 16 and Thomas et al reported the case of a 77‐year‐old man who was asymptomatic as an adult until the seventh decade when he developed biventricular failure 17 …”
Section: Discussionmentioning
confidence: 99%
“…15 Chin et al similarly reported the case of a 61-yearold man, 16 and Thomas et al reported the case of a 77-year-old man who was asymptomatic as an adult until the seventh decade when he developed biventricular failure. 17 Hokansen et al studied the published autopsy cases of patients with tetralogy of Fallot who died without any surgical treatment to determine the life expectancy of such persons. The survival data indicated that 66% of persons with tetralogy of Fallot not treated surgically live up to the age of 1 year, 49% up to the age of 3 years, and 24% up to the age 10 years, with the chance of survival significantly less when pulmonary atresia, rather than stenosis, is present.…”
Section: Discussionmentioning
confidence: 99%